Effect of chloride salt type on the physicochemical, mechanical and morphological properties of fish gelatin film. (27th November 2019) - Yu, Hong; Peng, Chun; Li, Fa-Cai; Yu, Peng
Abstract: Fish gelatin (FG) film has received an increasing attention in the last decades due to its biodegradability and environmental friendliness, which is a prospective replacer of petroleum-based plastics. This work for the first time investigated the effect of chloride salt type on the properties of the FG film. FG films incorporated with three kinds of chloride salts (CaCl2, KCl, NaCl) with various concentrations were prepared by casting. The light barrier property, mechanical property, swelling behaviour, color and scanning electron microscopic (SEM) micrographs of FG films were investigated. The incorporation of CaCl2 had no effect on the light barrier property and the color of FG films, while the addition of NaCl or KCl increased the resistance of FG films to ultraviolet and visible light. The incorporation of KCl or NaCl decreased the tensile strength (TS) and elongation at break (EB) of FG films significantly while the EB of FG films increased with the addition of CaCl2 . There is no significant difference on the swelling of FG films after incorporation of CaCl2 . However, the incorporation of KCl or NaCl could significantly increase the swelling value of FG film at the high level of chloride. SEM micrographs showed that CaCl2 was most compatible with gelatin protein among three kinds of chloride salts. These results may cause the extensive concern for the effects of salts on FG films because salts exist widely.